On the fluorescence enhancement mechanism of Er^3＋ in germanate glass containing silver particles - 李香萍 陈宝玖 申人升 张金苏 孙佳石 程丽红 仲海洋 田跃 付少博 杜国同 (中国物理B：英文版, 2013)
The spectral properties of trivalent erbium ions（Er^3＋） are systematically studied in a melt-quenched germanate glass（60 GeO2-20PbO-10BaO-10K2O-0.1Ag2O） containing silver（Ag） particles.Thermal treatment of the material leads to the precipitation of Ag particles as observed by transmission electron microscopy and confirmed by absorption spectrum for the obvious surface plasmon resonance peak of Ag particles.The fluorescence from Er^3＋ in the 10-min-annealed sample with Ag particles is found to be 4.2 times enhanced compared with the unannealed sample excited by 488-nm Ar＋ laser.A comparison is made between a spectral study performed on the unannealed Er^3＋-doped sample and the one annealed for 20 min.The data of absorption cross section and Judd-Ofelt intensity parameters show the agreement between the two samples no matter whether there are Ag particles,indicating that the introduction of Ag particles by post-heat treatment has no effect on the crystal field environment of Er^3＋ ions.The fluorescence enhancement is attributed to the surface plasmon oscillations of Ag particles in germanate glass.